Activated protein C promotes neuroprotection: mechanisms and translation to the clinic. Issue 141 (May 2016) - Griffin, John H.; Fernández, José A.; Lyden, Patrick D.; Zlokovic, Berislav V.
Abstract: Activated protein C (APC) is a plasma serine protease that is capable of antithrombotic, anti-inflammatory, anti-apoptotic, and cell-signaling activities. Animal injury studies show that recombinant APC and some of its mutants are remarkably therapeutic for a wide range of injuries. In particular, for neurologic injuries, APC reduces damage caused by ischemia/reperfusion in the brain, by acute brain trauma, and by chronic neurodegenerative conditions. For these neuroprotective effects, APC requires endothelial cell protein C receptor. APC activates cell signaling networks with alterations in gene expression profiles by activating protease activated receptors 1 and 3. To minimize APC-induced bleeding risk, APC variants were engineered to lack > 90% anticoagulant activity but retain normal cell signaling. The neuroprotective APC mutant, 3K3A-APC which has Lys191–193 mutated to Ala191–193, is very neuroprotective and it is currently in clinical trials for ischemic stroke.